Fatwa On The Opinion Of Contemporary Scholars On Stock Buying And Selling Activities In The Sharia Capital Market - Hardiati, Neni; Fitriani; Wahyu Nugroho (PT. Banjarese Pacific Indonesia, 2024)
According to contemporary scholars, buying and selling shares is of the opinion that buying and selling shares is legally permissible and some are prohibited. Meanwhile, according to the DSN Fatwa, ensuring share buying and selling transactions are halal. Buying and selling shares from an Islamic legal perspective is an important topic in integrating modern economic practices with sharia principles. The analysis includes the definition of shares as ownership of company assets, the importance of ensuring that the company's business is halal, as well as the prohibition against usury and gharar. Differences of opinion among scholars in determining the law itself. This research aims to compare the opinions of the DSN Fatwa with Contemporary Fuqaha in determining the law on the sale and purchase of shares. The approach used in this writing is a normative juridical approach with literature studies. The results that the author can conclude are that the law on buying and selling shares is permissible and some is prohibited.